ADAPTATION OF STUDENTS TO THE PROFESSIONAL ACTIVITY OF THE CIVILIAN OPERATIONAL AND RESCUE SERVICE PROTECTION OF THE MOE OF EMERGENCY OF UKRAINE (Pedagogy of Higher and Secondary Education, 2009)
It deals with the adaptive and developing conception of cadets' socialization in course of studying at fire fighting technical higher educational.